The Blessed Egidius, the native of Athens and the Saint of France - Natalya Gvozdetskaya (Вестник Православного Свято-Тихоновского гуманитарного университета: Сериа III. Филология)
This paper deals with an anonymous Old English version of the Life of St. Giles (Egidius) which is regarded as a rendering of the contemporary but not extant Latin version. St. Giles, a native of Athens and the fi rst abbot of the monastery of Saint-Gilles-du-Gard (late 7th c.), became known in England through close contacts of the English Church hierarchy with France after the Norman Conquest. St. Giles as an ascetic seeking to follow the Gospel commandments was in tune with the era of the Benedictine Revival of the monasticism which was trying to free itself from the influence of secular magnates. The Old English Life, the fi rst vernacular rendition of the legend of St. Giles found in a manuscript of the mid-12th c., is considered to be a fairly accurate copy of the Old English original text of the late 11th c. Although the language of the work is predominantly West Saxon written standard, it shows a number of deviations characteristic of Early Middle English, including Scandinavian loanwords borrowed from the spoken language. The anonymous author follows his Latin source rather accurately (its closest analogue is one of the manuscripts of the British Library) but in some cases alters, abbreviates or expands it. The substitution of Eusebius for Caesarius (the bishop of the 6th c.) can be associated with the desire to make the story more truthful. The alterations primarily concern Latin rhetoric, historical or biblical details while the additions emphasise the more personal and loving relationship that the saint has with God, which is usually explained by the didactic function of the text or the increasing role of an individual in the religious life of the West. This edition is the fi rst translation of the Old English Life of St. Giles into Russian.